Investigation on corona performance of conductors using fabricated indoor corona cage. (2021) - Megala, V.; Karpagam, R.; Sathishkumar, G.K.; Gopinath, B.; Marish Kumar, P.; Deva Brindha, M.
Abstract: An indoor corona cage (CC) is designed to study the performance of corona discharge. The design criteria of CC and their test results are presented. The HVAC, HVDC positive and negative excited conductors' corona characters are compared. The corona losses are calculated and compared for HVAC and HVDC supply. The conductors are tested for different surface condition, different dimensions, different atmospheric condition, on different materials and different stranded conductors and their results are analysed.